A current-mode four-phase third-order quadrature oscillator using a MCCCFTA - Kumngern, Montree; Torteanchai, Usa (My University, 2012)
This paper presents a new current-controlled current-mode third-order quadrature oscillator. The proposed circuit employs only one modified current-controlled current follower transconductance amplifier (MCCCFTA) and three grounded capacitors which is highly suitable for integrated circuit implementation. Also four quadrature current output terminals possess high impedance level which can be directly connected to the next stage without additional follower circuits. The condition of oscillation and the frequency of oscillation can be controlled orthogonally and electronically by adjusting the biasing currents of the MCCCCFTA. Simulation results verifying the theoretical analysis are included. © 2012 IEEE.
Keywords: Current-mode circuit; Modified current-controlled current follower transconductance amplifier; Quadrature oscillator